2006
DOI: 10.1007/s00221-006-0522-7
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic instabilities in albinism without nystagmus

Abstract: Albinism effects a surprising manipulation of the visual pathway in which some of the normally uncrossed axons of the temporal retina instead cross at the chiasm. An expected consequence of this misrouting is that subjects with albinism will have difficulty in specifying the targets of saccades. Usually albinos have nystagmus so the stability of their saccadic eye movements is not readily accessible, but some albinos do not have nystagmus. In these subjects it was found that they had frequent saccadic intrusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“… 5 7 Even patients with albinism and no clinically detectable nystagmus were shown to have significant saccadic instabilities. 8 While there are a number of genes associated with different forms of albinism, the lack of pigmentation in these individuals leads to foveal hypoplasia and abnormal routing of the optic nerves. 9 , 10 In addition, it has been shown in animal models of albinism that the optic nerves contain a population of abnormal axons.…”
mentioning
confidence: 99%
“… 5 7 Even patients with albinism and no clinically detectable nystagmus were shown to have significant saccadic instabilities. 8 While there are a number of genes associated with different forms of albinism, the lack of pigmentation in these individuals leads to foveal hypoplasia and abnormal routing of the optic nerves. 9 , 10 In addition, it has been shown in animal models of albinism that the optic nerves contain a population of abnormal axons.…”
mentioning
confidence: 99%
“…They are usually seen in association with cerebellar diseases that involve the fastigial nucleus or its outputs. They may be seen in patients with albinism [50] and, rarely, in patients with lesions in the pons in the vicinity of the omnipause neurons [51]. Based on the findings of recent modeling studies, it has been suggested that macrosaccadic oscillations arise due to a delay in the choking of saccadic drive signals by the fastigial nuclei of the cerebellum [9••].…”
Section: Macrosaccadic Oscillationsmentioning
confidence: 99%
“…Pattern appearance and flash stimuli have been typically used in most electrophysiological studies of chiasmal misrouting in albinism as prVEP responses can be confounded by nystagmus, which is present in the majority of people with albinism [16,21]. Although potentially under diagnosed, albinism without nystagmus is relatively rare, occurring in 6% to 11% of people with albinism [22,23]. Monocular hemifield (HF) prVEP stimulation is a sensitive way to identify hemisphere and chiasmal dysfunction in patients with steady central fixation [24,25].…”
Section: Introductionmentioning
confidence: 99%